#2**+1 **

Hey there, Guest!

This equation isn't tough, so I'll walk you through it step-by-step.

Step 1: Simplify both sides of the equation

3t−2+4=t−7t

3t+−2+4=t+−7t

(3t)+(−2+4)=(t+−7t)(Combine Like Terms)

3t+2=−6t

3t+2=−6t

Step 2: Add 6t to both sides.

3t+2+6t=−6t+6t

9t+2=0

Step 3: Subtract 2 from both sides.

9t+2−2=0−2

9t=−2

Step 4: Divide both sides by 9.

\(9t/9 = −2/9 \)

\(t= −2/9 \)

And as you can see, t equals \(-2/9\).

Hope this helped! :)

( ﾟдﾟ)つ Bye

TaliaArticula Apr 4, 2021